The Influence of Customer Satisfaction and its Determinants in Using Mobile Banking Services - Hidayat, Arynda Syavina; Pusparini, Herlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of trust, convenience, security, and transaction speed on customer satisfaction in the use of mobile banking in the city of Mataram. This research was conducted in the city of Mataram using convenience sampling techniques. In this study, primary data was used. The data analysis method used is SEM-PLS (Partial Least Square) with the help of the WarpPLS 8.0 statistical tool. The results of this study show that there is a positive and significant influence between the variables of trust, convenience, security and transaction speed on customer satisfaction.